Development of Android-Based LIBRA (Layanan Dasar Klasikal Berbasis Android) at State Junior High School 3 Palangka Raya - Fendahapsari Singgih Sendayu; Muhamad Romadoni; Eka Rohma Dhani (Universitas PGRI Yogyakarta, 2026)
The implementation of counseling services at State Junior High School 3 in Palangka Raya remains conventional. This affects students' interest in following the service. This research aims to develop an Android-based application named LIBRA. The research method used is Research and Development with the ADDIE development model. The LIBRA application was tested by one material expert, one media expert, and two expert practitioners. Data analysis techniques used for expert testing include Aiken's V formula, the Wilcoxon Test, and the Effect Size Test. The results of the feasibility test of the LIBRA application and its guidelines, accumulated from media experts, yield a coefficient value of 1.05; from material experts, 1.165; and from expert practitioners, 1.225. All experts showed a high level of relevance. The Wilcoxon test results give Asymp. Sig. Values. (2-tailed) with a score of 0.020. Meanwhile, the effectiveness test in small groups shows an effect size of 0.875, indicating that the LIBRA application has a strong effect on the implementation of basic classical guidance services. This has an impact on students' interest and on the quality of counseling services at school. Keywords: applications, classic basic services, guidance and counseling